PENGEMBANGAN MASYARAKAT ISLAM DAN OPTIMALISASI HUMAN CAPITAL MANAGEMENT SEBAGAI MODEL INVESTASI JANGKA PANJANG PARTAI POLITIK DPC PDIP KABUPATEN PESAWARAN - Aria Guna; Marzuki Noor (Program Studi Pengembangan Masyarakat Islam STID Mohammad Natsir, 2026)
The development of Islamic society is one of the key strategies in building sustainable political strength, especially in areas that have a dominant Muslim voter base such as Pesawaran Regency. Optimizing Human Capital Management (HCM) is seen as an approach that can strengthen the capacity of cadres, improve the quality of socio-religious services, and create long-term political investment for the party. This research uses a qualitative-descriptive method with a literature study and policy analysis approach, through tracing the organizational documents of the DPC PDIP Pesawaran, HCM theories, and literature on the development of Islamic society. The analysis was carried out through data reduction, thematic categorization, and theoretical interpretation based on the HCM framework and the concept of community empowerment based on Islamic values. The results of the study show that HCM optimization provides three strategic contributions: (1) strengthening cadre competencies through political education, technical training, and internalization of national-Islamic values; (2) increasing the effectiveness of Islamic community development programs through a participatory, inclusive, and needs-based approach of the ummah; and (3) the birth of a long-term political investment model that increases the legitimacy and competitiveness of the party. These findings confirm that HCM not only strengthens the internal structure of party organizations, but also becomes a key instrument in building collaborative relationships and the sustainability of Islamic community empowerment programs at the local level. This study emphasizes the urgency of systematic, measurable, and future-oriented HR governance for political parties in developing a more adaptive, productive, and responsive political approach to the needs of the Muslim community.